Photo‐Curable Ion‐Enhanced Fluorinated Elastomers for Pressure‐Sensitive Textiles. (20th February 2020) - Chen, Guan-Ting; Su, Chun-Hao; Wei, Shih-Han; Shen, Tien-Lin; Chung, Pei-Hsuan; Guo, Qiao-Miao; Chen, Wei-Jen; Chen, Yang-Fang; Liao, Ying-Chih; Lee, Wen-Ya
Abstract : Smart textiles integrated with the function of recording tactile stimulation attract much attention due to its great potential for health monitoring and wearable electronics. However, the highly uneven surface and poor thermal stability of textiles become main challenges for precision measurement and device fabrications. To solve these issues, an ion‐assisted pressure‐sensitive textile using a novel photo‐curing process is demonstrated in this work. Using a photo‐cured fluorinated polymer poly(vinylidene fluoride‐ co ‐hexafluoropropene) (PVDF‐HFP) and a transparent polydimethylsiloxane (PDMS) mold, a highly sensitive pyramid array of PVDF‐HFP is successfully fabricated on a textile. Furthermore, after doping the ionic additive, tetrabutylammonium perchlorate (TBAP), the sensors show improved sensitivity due to the enhanced dielectric constant. The dielectric constant has a significant increase in the value over 37 after doping a small amount of TBAP (2 wt%). Due to the ion doping, the sensitivity of the textile pressure sensors show significant improvement (0.73 kPa −1 ) higher than that of the PDMS‐based one (0.19 kPa −1 ). This work not only opens an efficient approach for the fabrication processes of a high‐k elastomer pyramid array on a textile but also provide a design strategy to improve performance of capacitive pressure sensor for smart textiles. Abstract : Smart textiles integrated with capacitive pressure sensors are highly desirable for next‐generation wearable electronics. However, the highly uneven surface and poor thermal stability of textiles causes low pressure sensitivity and device instability. To solve these issues, an ion‐assisted pressure‐sensitive textile using a novel photo‐curing process is demonstrated to improve sensitivity and device stability.